2018
DOI: 10.1063/1.5021181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the screened Coulomb disorder on magneto-transport in Weyl semimetals

Abstract: The observation of negative longitudinal magnetoresistivity (NLMR) in Weyl semimetals has gained strong support in recent experiments. It is believed that charged impurities play an important role in the measurement of NLMR. We thus employ a screened Coulomb disorder to model charged impurities and derive a general screening length depending on the magnetic field, chemical potential and temperature. We study the magneto-transport in a two-node Weyl semimetal in which the intra-valley scattering and the inter-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For shortrange point impurities, the longitudinal magnetoconductance can be either negative if the dependence of the Fermi velocity on the magnetic field is included [19][20][21], or constant if the Fermi velocity does not depend on the magnetic field [22,23]. Gaussian impurities usually cause a positive linear longitudinal magnetoconductance [19,[22][23][24] and in the presence of screened but not pointlike Coulomb scattering, the longitudinal magnetoconductance is expected to be positive and quadratic [19,[23][24][25].…”
mentioning
confidence: 99%
“…For shortrange point impurities, the longitudinal magnetoconductance can be either negative if the dependence of the Fermi velocity on the magnetic field is included [19][20][21], or constant if the Fermi velocity does not depend on the magnetic field [22,23]. Gaussian impurities usually cause a positive linear longitudinal magnetoconductance [19,[22][23][24] and in the presence of screened but not pointlike Coulomb scattering, the longitudinal magnetoconductance is expected to be positive and quadratic [19,[23][24][25].…”
mentioning
confidence: 99%
“…On the theoretical front, it is also now established that Weyl nodes may not always result in a positive LMC. For strong magnetic fields (when Landau quantization is relevant), LMC can be either positive or negative for short-range scatterers, while it is usually positive for charged impurities [50][51][52][53][54][55][56]. In the weak magnetic field regime, it was believed that the LMC is positive [57][58][59][60][61][62][63][64], however a recent study by Knoll et al (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, a detailed analysis shows that positive longitudinal magnetoconductance is neither a necessary, nor a sufficient condition to prove the existence of chiral anomaly in WSMs. It has now been well established that both positive or negative magnetoconductance can arise from chiral anomaly in WSMs [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. In the presence of strong magnetic field, when Landau quantization is relevant, the sign of magnetoconductance depends on the nature of scattering impurities [49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…It has now been well established that both positive or negative magnetoconductance can arise from chiral anomaly in WSMs [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. In the presence of strong magnetic field, when Landau quantization is relevant, the sign of magnetoconductance depends on the nature of scattering impurities [49][50][51][52][53][54][55]. For weak magnetic fields, it was recently shown that sufficiently strong intervalley scattering can switch the sign of LMC [64,65].…”
Section: Introductionmentioning
confidence: 99%